COMMENTS ON THE ARTICLE: “AGENTS RELATED TO INFECTION OF THE OPERATING SITE IN POSTOPERATED MAJOR ADULTS IN THE NAVAL MEDICAL CENTER, 2013 - 2017”: COMENTARIOS SOBRE EL ARTÍCULO: “AGENTES RELACIONADOS A INFECCIÓN DE SITIO OPERATORIO EN ADULTOS MAYORES POS OPERADOS EN EL CENTRO MÉDICO NAVAL, 2013 – 2017” - Pulido Flores, Jordy (2019)
After reading this article with interest published by Hidalgo et al regarding agents related to the surgical site infection (SSI) in elderly between the years 2013 and 2017; we found the consideration of certain relevant determinants related to clinical and surgical aspects. These determinants are useful since they are taken as reference in future research work. Nevertheless, we would like to emphasize the necessity to incorporate some other relevant variables as possible determinants to control such as those related to nutritional status specifically hemoglobin and preoperative albumin levels since in our country this kind of pathologies is common. In different countries, SSI is one of the most deadly and costly complications increasing mortality from 2 to 11 times and the cost to 14.2 million dollars in surgeries4. In Peru, from 15 000 nosocomial infections, 30, 9 % are from an surgical wound5. It is important to know the details of this theme because it contributes to a highly reversible social and economic problem.